2016
DOI: 10.3390/life6020015
|View full text |Cite
|
Sign up to set email alerts
|

tRNA Core Hypothesis for the Transition from the RNA World to the Ribonucleoprotein World

Abstract: Herein we present the tRNA core hypothesis, which emphasizes the central role of tRNAs molecules in the origin and evolution of fundamental biological processes. tRNAs gave origin to the first genes (mRNA) and the peptidyl transferase center (rRNA), proto-tRNAs were at the core of a proto-translation system, and the anticodon and operational codes then arose in tRNAs molecules. Metabolic pathways emerged from evolutionary pressures of the decoding systems. The transitions from the RNA world to the ribonucleopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Similar results were found in a separate study [63]. These remarkable results suggest both tRNA and tRNA ribosomal relics hold deep phylogenetic information indicating they both stored genetic information for ancient proteins and acted as ancient genomes.…”
Section: Genomic Accretion Of Trna Building Blockssupporting
confidence: 87%
“…Similar results were found in a separate study [63]. These remarkable results suggest both tRNA and tRNA ribosomal relics hold deep phylogenetic information indicating they both stored genetic information for ancient proteins and acted as ancient genomes.…”
Section: Genomic Accretion Of Trna Building Blockssupporting
confidence: 87%
“…Then, analyzes of sequences and secondary structures of ribosomes suggested that these derived from tRNAs also functioned as a protogenome [82]. The very parsimonious syncretic model "tRNA core hypothesis" assumes that some proto-tRNAs were classical tRNAs and also functioned as rRNAs and mRNAs, a self-recognition between these molecules allowed to obtain proto-proteins [88].…”
Section: Trnas At the Origin Of All The Nucleic Members Of The Rna/prmentioning
confidence: 99%
“…This leads us back to the idea of a proto-ribosome preceding the LUCA (Fox 2016b;Fox and Naik 2004;Bowman et al 2015). In one novel hypothetical scenario, ancient versions of transfer RNAs (tRNA) could enable the origin of the first genes (mRNA), while a proto-PTC (rRNA) and proto-tRNAs formed a proto-translation system, followed by the emergence of metabolic pathways (de Farias et al 2016). In addition to what was mentioned earlier about the protoribosome, it has been shown that a quantum mechanical theoretical model of such a system based on coordinates of known crystal structures of existing ribosomes, fits well with energetic stability of such a proto-ribosome structure and its attachment to substrates (Huang et al 2013).…”
Section: Molecular Mutualism or Symbiosis Between Polymers Of Nucleotmentioning
confidence: 99%